Scramasax The Viking sagas - Crossley-Holland, Kevin 1941- (The Viking sagas, 2012)
Solveig has made it all the way from Norway to the glittering city of Constantinople, where her father is a member of the guard of Empress Zoe. Soon Solveig finds herself caught up in the conflict between the Viking guard and the Islamic people of nearby Sicily